Piccole ‘curiosità’ delle religioni antiche. Un approccio antropologico (Firenze University Press, USiena Press, 2026)
Studying ancient religions often means facing objects, gestures, and ritual formulas that appear “curious” or even “strange”. It is precisely these “strangenesses” that give anthropological inquiry its strength: they reveal cultural distance and invite us to understand them within their historical and social context. This volume reflects on such “curiosities”: Roman legal norms allowing gods to inherit, objects safeguarding Rome’s stability, relics of foundational moments, “sweeper” deities, the agency of fabrics, a Phoenician god with a feminine name, Jewish dietary prohibitions, and small Mexican gods made of amaranth. How were these perceived? What was their meaning? To grasp them, we must try to see with the eyes of the cultures that produced them.